Cutaneous Changes Beyond Psoriasis: The Impact of Biologic Therapies on Angiomas and Solar Lentigines - Florin Ciprian Bujoreanu; Diana Sabina Radaschin; Ana Fulga; Laura Bujoreanu Bezman; Carmen Tiutiuca; Mihaela Crăescu; Carmen Pantiș; Elena Niculet; Alina Pleșea Condratovici; Alin Laurențiu Tatu (Medicina)
Background and Objectives: Psoriasis is a chronic inflammatory skin disease, and biologic therapies have revolutionized treatment by targeting key cytokine pathways. While these therapies effectively control psoriatic lesions, their impact on other cutaneous structures, such as cherry angiomas and solar lentigines, remains unclear. Angiomas are benign vascular proliferations influenced by systemic inflammation and hormonal factors, whereas solar lentigines are UV-induced pigmentary lesions associated with aging and sun exposure. This study aimed to assess the impact of biologic therapies on the development of these lesions in psoriasis patients. Materials and Methods: This retrospective observational study was conducted over a five-year period (2019–2024) at a tertiary dermatological center in Southeastern Europe. Clinical and demographic data, including treatment history, were extracted from medical records, while digital dermoscopy was used to assess lesion progression. Statistical analyses evaluated associations among biologic therapy classes, systemic inflammation, and cutaneous lesion development. Results: Angioma prevalence was significantly higher among postmenopausal women and those with osteoporosis, suggesting a hormonal influence on vascular proliferation. Patients with psoriatic arthritis had a greater angioma burden, reinforcing the role of chronic inflammation in angiogenesis. IL-23 inhibitors were linked to increased angioma formation compared to TNF-α inhibitors, while methotrexate and UVB therapy appeared to have a protective effect. Solar lentigines were more frequent in postmenopausal women and in patients with systemic inflammatory conditions. In contrast, smoking and moderate alcohol consumption were associated with lower lesion counts. Conclusions: Our findings suggest that biologic therapies, particularly IL-23 inhibitors, may contribute to angiogenesis and pigmentary changes in psoriasis patients, highlighting the influence of systemic inflammation on vascular and melanocytic activity. Additionally, TNF-α inhibitors and NSAIDs were associated with an increased prevalence of solar lentigines, while methotrexate and UVB therapy appeared to have a protective effect. Given these associations, further research is needed to elucidate the underlying mechanisms and refine treatment strategies to optimize dermatologic care for psoriasis patients.